Clinical Governance: The Need for New Directions in Canada: [Includes Principles to Guide Changes and Evaluation.] - Donald R. Carlow (Healthcare Quarterly, 2010)
As greater attention is paid to various facets of quality and safety within the Canadian healthcare system, it is important to understand the current state of clinical governance and clinical quality processes in Canada. Significant advances have been made internationally in understanding the important role of clinical governance in achieving quality and safety. It is clear, however, from various reports that major developments in clinical governance are needed if the quality and safety missions of governing boards of health authorities and other provincial and national bodies are to be achieved. In this paper, several key elements of an effective clinical governance system will be reviewed, some issues that characterize clinical governance in Canada will be raised and some principles that might help in evaluation and moving forward will be identified.
Keywords: Clinical Governance, Change, Evaluation, quality, health outcomes